Children’s humor development: A case of Indonesian children - Sahayu, Wening; Triyono, Sulis; Kurniawan, Eri; Baginda, Putrasulung; Tema, Nurul Huda Gus (Indonesian Journal of Applied Linguistics, 2022)
Humor has been characterized as an index of children’s language development and cognitive performance. While research on this area has been abound cross linguistically, specific inquiry on children’s humor development in the Indonesian context remains scant. Occupying this lacuna, this research sought to examine kinds of humor acquired by the children in early childhood by invoking McGhee’s humor developmental stages. Embracing a descriptive qualitative method, the study involved eleven Indonesian-speaking children in Yogyakarta aged around 1 to 5 years old, where the data were assembled primarily through direct naturalistic observations. The children’s spontaneous humor production was recorded as they were interacting with their peers and/or their parents in their homes and neighborhoods. The findings revealed that the children could perceive and produce nonverbal and verbal humor, confirming existing literature. As they grow, certain patterns of humor also emerge, indicative of their cognitive and social development. More research is necessary to better understand how children of different linguistic and cultural backgrounds understand, respond to or initiate a humorous situation.